The power of wood waste - Kompf, Michael
As oil gas prices continue to rise, biomass is becoming a more interesting energy source. In Traunreut, Bavaria, STEAG AG is producing electric power and energy for district heating from wood waste.
Keywords: Wood waste -- Traunreut, Bavaria; Biomass energy -- Traunreut, Bavaria; Waste products as fuel -- Traunreut, Bavaria